EFFECTIVENESS OF MASKS AND RESPIRATORS AGAINST RESPIRATORY INFECTIONS IN HEALTHCARE STAFF - Hamad Nasser Ali Al Alhareth , Safar Saleh Hamad Alhatheg, Mana Nasser AAlmansour, Makran Ahmad Al Makran Salha Naser Said Almabkhoot, Nasser Mubarak Abdullah Alsakoor, Sajwa Falah Hussain Al Makhalas,,; Ali Fares Hamad Alyami, Salim Salih M Al Khuraim, Raedah Ibrahim Alsaleh , (Chelonian Research Foundation, 2022)
Introduction: The global spread of respiratory infections, including influenza and COVID-19, poses significant risks to healthcare workers, underscoring the need for effective protective measures. This systematic review aimed to evaluate the effectiveness of masks and respirators in preventing respiratory infections among healthcare staff, providing evidence-bmsed recommendations to inform healthcare policies and practices. Methods: A comprehensive literature search was conducted across multiple databases, including PubMed, Cochrane Library, and Scopus, focusingon interventional studiesand clinical trials published up to 2022. 'Ihe review included studies that assessed the effectiveness of surgical masks, N95 respirators, and other protective memsures in healthcare settings. The selection process involved screening titles, abstracts, and full texts based on predefined inclusion and exclusion criteria, followed by quality assessment and data extraction performed independently by two reviewers. Results: Thirteen studies were included, with sample sizes ranging from 50 to over 2,000 participants. The findings revealed that N95 respirators significantly reduced the risk Of laboratory-confirmed respiratory infections among healthcare workers, with risk ratios ranging from 0.58 to 0.93, indicating a risk reduction Of up to 42% compared to surgical masks. Combined interventions, including mask use and hand hygiene, demonstrated a further reduction in infection risk. However, the effectiveness varied across different study designs and healthcare settings. Conclusions The systematic review highlights the importance of using appropriate personal protective equipment, particularly N95 respirators, in reducing the risk of respiratory infections among healthcare workers. The evidence supports a multifaceted approach to infection control, combining PPE with hand hygiene and other preventive mezusures. Despite sorne limitations, such as study heterogeneity and potential language bias, the findings contribute valuable insights for developing effective infection prevention strategies in healthcare environments. Keywords: Healthcare Workers, Respiratory Infections, Masks, Respirators, Systematic Review, Infection Control.